Juvenile justice (care and protection of children) act, 2015 (2 of 2015) - Shree ram law house; Bare Act (Chandigarh Shree Ram Law House, 2024)
The Juvenile justice (care and protection of children) act, 2015 (2 of 2015) as amended by The Juvenile Justice (care and protection of children) amendment act, 2021 (act no. 23 of 2021).
Keywords: Juvenile Justice Act; Care & Protection of Children Act